A study on the effects of grate setting and differential pressure on the performance of a downdraft gasifier - Lacson, Isaias T.
This study was conducted to determine the effects of varying grate position relative to the throat and varying differential manometer pressure on the performance of conventional downdraft gasifier, using ipil-ipil woodchips as biomass fuel. Results show that grate position and differential pressure have highly significant effect on the gasifier performance, particularly on the gas heating value, conversion efficiency, temperature in the reactor, and on the tar cracking capacity of a downdraft gasifier. Results also indicated that the tar conversion capability of the downdraft gasifier as indicated by the prediction equations for unaccounted carbon, hydrogen and oxygen, is highly dependent on the efficiency, grate setting, and temperature in the reactor specially in the combustion and reduction zones.